Women in The Shadow of Ideology: Women's Rights in North Korea - Lale, Aybala (My University, 2025)
Described as a 'closed box' in the interna- tional system, North Korea is characterized by a governing ideology that penetrates every aspect of life: Juche. Conceived as a philosophy of self-sufficiency, Juche helps North Korea maintain its authoritarian system. In this authoritarian and closed society, women are probably the most disadvantaged group. Indeed, North Korea is one of the world's worst human rights violators. The position of North Korean women, who were shaped as political actors, representatives of the revolution, and founding elements during the founding period of the country, has evolved in a completely different direction today. In the official discourse, women and mothers are used synonymously, but it is often stated that women should devote themselves entirely to the ideology and the leader's guidance. In addition to ideology, the hierarchical order of the Confucian system of thought that has influenced East Asian societies is also behind this idea. In these societies, a woman is obliged to obey her husband and is a mother. While the international community is preoccupied with the threat of North Korea becoming a nuclear power, the rights of North Korean women are ignored. The fact that the majority of North Koreans who defect today are women reveals the seriousness of the situation. This study examines how women's rights in North Korea are shaped within the framework of the Juche ideology. The study will focus on evaluating the discrepancy between the rights officially granted to women and how these rights are implemented in practice, while also analyz- ing the status of women under the influence of ideology. It aims to uncover the struggle of North Korean women, who are portrayed as integral to the socialist system, in their fight against oppression.
Keywords: Women; Human Rights; Women's Rights; North Korea; Juche Ideology